Enhancing Science Process Skills and Academic Performance in Biology: The Impact of Practical Work - Apeadido, Shine; Opoku-Mensah, Douglas; Mensah, Gabriel Opoku (Integrated Science Education Journal, 2024)
Purpose of the study: This study aims to determine whether the use of practical work can enhance General Science students’ science process skills acquisition and academic performance students in biology at Juaben Senior High School in Ghana. The study sought to answer two research questions and test one hypothesis at a 0.05 significance level. Methodology: The study used action research, and the sample consisted of 45 students, selected through convenience sampling. The study used various instruments, including pre- and post-tests, weekly intervention exercises, and scoring rubrics, to collect data. The analysis of the gathered data employed descriptive statistics and a paired sample t-test to reveal and solidify the findings of the study. Main Findings: According to the study’s results, the use of practical work resulted in a steady increase in students’ acquisition of science process skills in each cycle, and all students were able to demonstrate some degree of required science process skills at the post-test level in contrast to the pre-test level. Furthermore, the pre- and post-test outcomes of a paired sample t-test analysis with a 95% confidence level showed a significant improvement in the academic performance of the students, attributed to practical work. Novelty/Originality of this study: This research update confirms the need for practical work in biology education and shows that incorporating it into biology lessons enhances students’ acquisition and development of science process skills, which in turn enhances their academic performance.